Agronomic performance of common bean third crop under irrigation in the northwestern region of Paraná State - Gomes, Eder Pereira; Biscaro, Guilherme Augusto; Ávila, Marizangela Rizzatti; Loosli, Felipe Silva; Vieira, Camila Viana; Barbosa, André Prechlak (Semina: Ciências Agrárias, 2012)
This research was done to evaluate the yield and yield components of bean third crop under irrigation depths in the northwestern region of Paraná State. The experiment was conducted in Arenito Campus of the State University of Maringa, Cidade Gaúcha city. The research was implanted with six irrigation depths (0, 104.1, 171.8, 192.4, 222.9 and 333 mm) and four replicates with a randomized block design and plot banded. The plants number per meter (NPM), pods per plant number (NVP), grains per pod number (NGV), hundred grains weight (MCG), crop height (AP) and height of first pod (AIPV) were evaluated. The yield (PROD), pods per plant number (NVP), grains per pod number (NGV) and hundred grains weight (MCG) responded signicantly to irrigation depths. The highest yield, 2224 kg ha-1 was obtained with application of greater depth, equal to 333 mm.